Synthesis of sucrose partial esters of coconut oil. - Martinez, Adora May Daquiado
Sugar esters of coconut oil derived from the direct interesterification of coconut oil and sucrose is environmentally and economically friendly. Alakli metal soap and sodium metal were the catalyst used in the solvent less synthesis. Thin Layer Chromatography (TLC) and Fourier Transform Infrared Spectrometry (FTIR) were used to verify the product formed. Physical properties such as density, viscosity and surface tension, which are commonly and usually studied for fatty acid derivatives, were measured for further characterization of the product. The effect of the product on lowering the surace tension of water at different concentration levels was compared to tide powder with the same concentrations. Emulsifying activity was tested on oil-water, ethyl acetate-water, and N-hexane-water mixtures., Results of the synthesis gave approximately 46.46 percent yield based on the glyceride ester of lauric acid. At 31 degrees centigrade density, viscosity and surface tension of the product have values of 1.077 g/ml. 1,700 poises and 25.24 dynes/cm respectively. The surface tension of water (70.29 dynes/cm at 31 degrees centigrade) was lowered to 36.83 dynes/cm in the presence of 1 percent product compare to 30.93 dynes/cm of the Tide powder of the same concentration. At the same temperature, the surface tensions of the 2 percent and 3 percent product solutions were 34.30 dynes/cm and 30.18 dynes/cm respectively. While the Tide solution of the same concentrations have surface tension values of 29.70 and 28.06 dynes/cm respectively. The product also showed surface-active property by emulsifying mixtures of oil and water, ethyl acetate and water, and N-hexane and water.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Coconut oil